Factors influencing the re-emergence of plague in Madagascar. Issue 4 (1st December 2020) - Alderson, Jennifer; Quastel, Max; Wilson, Emily; Bellamy, Duncan
Abstract : Plague is an infectious disease found worldwide and has been responsible for pandemics throughout history. Yersinia pestis, the causative bacterium, survives in rodent hosts with flea vectors that also transmit it to humans. It has been endemic in Madagascar for a century but the 1990s saw major outbreaks and in 2006 the WHO described the plague as re-emerging in Madagascar and the world. This review highlights the variety of factors leading to plague re-emergence in Madagascar, including climate events, insecticide resistance, and host and human behaviour. It also addresses areas of concern for future epidemics and ways to mitigate these. Pinpointing and addressing current and future drivers of plague re-emergence in Madagascar will be essential to controlling future outbreaks both in Madagascar and worldwide.